Strategies for Learning the Recitation Al-Qur’an during a Pandemic at TPA Baiturrohman Kramat Lamongan - Anwar Mujahidin; Nur Hamidah Irba'ul Khair; Kelik Wardiono; Arif Budiono (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Baiturrohman al-Qur'an Education Park in Kramat Lamongan Village was established as a place for education to read the Koran and Islamic materials starting from kindergarten, elementary School/MI and higher education. However, the pandemic and the very strict emergency PPKM implementation policy caused face-to-face learning activities to be switched online (via WhatsApp groups). This has a significant effect on reducing student interest in learning. For this reason, through this KPM-DDR activity, researchers aim to find the best solution to increase interest in learning to read the Koran. In carrying out this community service, the ABCD approach is carried out by utilizing the potential/assets owned by the community by applying the five principles of discovery, dream, design, define and destiny. The results showed that the combination of limited online and face-to-face methods (divided into 3 groups) succeeded in increasing student interest.